Racial and ethnic disparities in telehealth use before and after California's stay-at-home order - Bustamante, Arturo Vargas; Martínez, Laura E.; Jalal, Siavash; Benitez Santos, Nayelie; Félix Beltrán, Lucía; Rich, Jeremy; Anaya, Yohualli Balderas-Medina (Frontiers in Public Health, 2023)
Telehealth can improve the quality of health care through increased access to primary care. While telehealth use increased during the COVID-19 pandemic, racial/ethnic disparities in the use of telemedicine persisted during this period. Little is known about the relationship between health coverage and patient race/ethnicity after the onset of COVID-19. We examine how differences in patient race/ethnicity and health coverage are associated with the number of in-person vs. telehealth visits before and after California's stay-at-home order (SAHO). We use weekly patient visit data (in-person (N = 63, 491) and telehealth visits (N = 55, 472)) from seven primary care sites of an integrated medical group in Los Angeles County to examine differences in telehealth visits reported for patients with chronic conditions (type 2 diabetes, prediabetes, and hypertension). After adjusting for age and sex, we estimate differences by race/ethnicity and the type of insurance using an interrupted time series with a multivariate logistic regression model. Our descriptive analysis shows that telehealth visits increased immediately after the SAHO for all race/ethnicity groups. Our adjusted analysis shows that the likelihood of having a telehealth visit was lower among uninsured patients and those with Medicaid or Medicare coverage compared to patients with private insurance. Latino and Asian patients had a lower probability of telehealth use compared to white patients. To address access to chronic care management through telehealth, we suggest targeting efforts on uninsured adults and those with Medicare or Medicaid coverage, who may benefit from increased telehealth use to manage their chronic care.